Sediment Barriers’ Performance in the Laboratory: Evaluation of Clogging and Filtration Characteristics in Geotextiles Subjected to Discharge Cycles - Adachi, Vitor Yudi Góes [UNESP]; Rodríguez, Joan Steven Flores [UNESP]; Motta, Mariana Ferreira Benessiuti [UNESP]; Pedroso, Gabriel Orquizas Mattielo [UNESP]; Hein, Luis Rogerio de Oliveira [UNESP]; Félix, Emerson Felipe [UNESP] (MDPI, 2024)
This research aims to assess the clogging process of geotextiles within silt fences. For that purpose, the filtering efficiency, flow rate, and clogging of three geotextiles (GTX-1, GTX-2, and GTX-3) employing two distinct soils and under three sediment discharge cycles were investigated. The analysis adhered to the American standard D5141-11 and, as further analyses, qualitative and quantitative inspections were conducted through microscopic images of the materials. The results showed greater clogging of the nonwoven geotextile, GTX-1, with higher retention efficiency (approximately 100%) and better turbidity removal for both soils, equal to a reduction of around 94%. For GTX-2, a woven geotextile with a larger pore opening, less intense clogging and lower retention efficiency were observed after the third discharge; the average was 96% for both soils. GTX-3, a woven geotextile with a smaller apparent opening, exhibited a behavior similar to GTX-1: as the number of cycles increased, the material experienced more clogging and higher retention efficiency for soil 1 (approximately 98.5%). Based on these findings, it can be inferred that the discharge cycles impact the tested geotextiles in diverse ways and, therefore, the selection of the material should be contingent on project requirements.
Keywords: discharge cycles; erosion; geotextile; optical microscopy; runoff; sediment barriers